2019
DOI: 10.3389/fimmu.2019.01452
|View full text |Cite
|
Sign up to set email alerts
|

Functional Enrichment and Analysis of Antigen-Specific Memory B Cell Antibody Repertoires in PBMCs

Abstract: Phenotypic screening of antigen-specific antibodies in human blood is a common diagnostic test for infectious agents and a correlate of protection after vaccination. In addition to long-lived antibody secreting plasma cells residing in the bone marrow, memory B cells are a latent source of antigen-experienced, long-term immunity that can be found at low frequencies in circulating peripheral blood mononuclear cells (PBMCs). Assessing the genotype, clonal frequency, quality, and function of antibodies resulting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…Accordingly, we obtained 8-fold more unique VH sequences from stimulated PBMCs with a greater representation of IgG over IgM clonal families compared to unstimulated PBMCs (Table S2). Compared to previously described healthy BCR repertoire data (Waltari et al, 2019), VH1-69, VH3-30, VH3-30-3, VH4-34, VH4-39 and VH4-59 were the most dominant across both unstimulated and stimulated PBMC VH families in patient 013 (average >= 5% of repertoire; Figure S10).…”
Section: Lineage Analysis Reveals Memory Origin and Divergent Evoluticontrasting
confidence: 48%
See 4 more Smart Citations
“…Accordingly, we obtained 8-fold more unique VH sequences from stimulated PBMCs with a greater representation of IgG over IgM clonal families compared to unstimulated PBMCs (Table S2). Compared to previously described healthy BCR repertoire data (Waltari et al, 2019), VH1-69, VH3-30, VH3-30-3, VH4-34, VH4-39 and VH4-59 were the most dominant across both unstimulated and stimulated PBMC VH families in patient 013 (average >= 5% of repertoire; Figure S10).…”
Section: Lineage Analysis Reveals Memory Origin and Divergent Evoluticontrasting
confidence: 48%
“…Given its greater junctional diversity compared to light chain, we focused our analysis on the heavy chain repertoire, which is sufficient to identify clonal relationships (Zhou & Kleinstein, 2019). We have recently shown that PBMC stimulation in a polyclonal, BCR-independent manner can selectively expand antigen-specific memory B cells (Waltari, McGeever, Friedland, Kim, & McCutcheon, 2019). Accordingly, we obtained 8-fold more unique VH sequences from stimulated PBMCs with a greater representation of IgG over IgM clonal families compared to unstimulated PBMCs (Table S2).…”
Section: Lineage Analysis Reveals Memory Origin and Divergent Evolutimentioning
confidence: 99%
See 3 more Smart Citations